2022
DOI: 10.1101/2022.07.12.499826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neonatal hyperoxia induces sex-dependent pulmonary cellular and transcriptomic changes in an experimental mouse model of bronchopulmonary dysplasia

Abstract: Hyperoxia (HOX) disrupts lung development in mice and causes bronchopulmonary dysplasia (BPD) in neonates. To investigate sex-dependent molecular and cellular programming involved in HOX, we surveyed the mouse lung using single cell RNA sequencing (scRNA-seq), and validated our findings in human neonatal lung cells in vitro. HOX-induced inflammation in alveolar type (AT) 2 cells gave rise to damage associated transient progenitors (DATP). It also induced a new subpopulation of AT1 cells with reduced expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
1
1
0
Order By: Relevance
“…We also observed changes in the pulmonary transcriptome and related regulatory pathways (Fig. S1) that are consistent with similar observations [9][10][11][12] showing type 2 immune polarization and extensive alterations in alveolar epithelial and endothelial cell populations in response to hyperoxia-induced lung injury.…”
Section: Hyperoxia Exposure Alters Lung Morphology and Functionsupporting
confidence: 90%
“…We also observed changes in the pulmonary transcriptome and related regulatory pathways (Fig. S1) that are consistent with similar observations [9][10][11][12] showing type 2 immune polarization and extensive alterations in alveolar epithelial and endothelial cell populations in response to hyperoxia-induced lung injury.…”
Section: Hyperoxia Exposure Alters Lung Morphology and Functionsupporting
confidence: 90%
“…Finally, we identified that the specific intercellular communication networks and the ligand-receptor pairs that are impacted by neonatal hyperoxia exposure. Xia et al have reported sex-specific differences in the lung cell sub- populations using different hyperoxia exposure model using 85% FiO2 for 14 days after birth (115).…”
Section: Discussionmentioning
confidence: 99%